Cycloaddition of alkynes to diimino Mo3S4 cubane-type clusters: a combined experimental and theoretical approach. (1st August 2016) - Pino-Chamorro, Jose A.; Laricheva, Yuliya A.; Guillamón, Eva; Fernández-Trujillo, M. Jesús; Bustelo, Emilio; Gushchin, Artem L.; Shmelev, Nikita Y.; Abramov, Pavel A.; Sokolov, Maxim N.; Llusar, Rosa; Basallote, Manuel G.; Algarra, Andrés G.
Abstract : Newly synthesised molibdenum diimino clusters interact with alkynes leading to dithiolene species. Abstract : A heterocyclic ligand 4, 4′-di- tert -butyl-2, 2′-bipyridine (dbbpy) has been coordinated to the Mo3 S4 cluster unit affording the complex [Mo3 S4 Cl3 (dbbpy)3 ] + ([1 ] + ) in a one-step ligand-exchange protocol from [Mo3 S4 (tu)8 (H2 O)]Cl4 ·4H2 O (tu = thiourea). The new cluster was isolated as [1 ]PF6 and [1 ]Cl salts in high yields and the crystal structure of the latter determined by X-ray analysis. The synthetic procedure was extended to tungsten to afford [W3 S4 Cl3 (dbbpy)3 ] + ([2 ] + ). Kinetic and NMR studies show that [1 ] + reacts with several alkynes to form dithiolene species via concerted [3+2] cycloaddition reactions whereas [2 ] + remains inert under similar conditions. The different rates for the reactions of [1 ] + are rationalised by computational (DFT) calculations, which show that the more electron-withdrawing the substituents of the alkyne the faster the reaction. The inertness of [2 ] + is due to the endergonicity of its reactions, which feature Δ G r values systematically 5–7 kcal mol −1 more positive than for those of [1 ] + .